Description of Nola estonica sp. nov., with comparison to N. aerugula and N. atomosa stat. rev. (Lepidoptera, Nolidae, Nolinae) - Õunap, Erki; Choi, Sei-Woong; Matov, Alexey; Tammaru, Toomas (Zootaxa, 2021)
Nola estonica Õunap sp. nov. (Lepidoptera, Nolidae, Nolinae) is described based on type material from Estonia. The lectotype is designated for Glaphyra atomosa Bremer, 1861, which is reinstated from a subspecies of Nola aerugula (Hübner, [1793]) to a full species: Nola atomosa (Bremer, 1861) stat. rev. The status of these three taxa as separate species is supported by the results of phylogenetic analysis of DNA barcodes, as well as external and genital morphology of adult specimens. Two new synonyms are established as follows: Nola atomosa (Bremer, 1861) = Nola candidalis Staudinger, 1892 syn. nov. and Nola shin Inoue, 1982 syn. nov. N. estonica occurs sympatrically with N. aerugula in Estonia, and with N. atomosa in South Korea and easternmost Russia. While the available data suggest a disjunct distribution of N. estonica (eastern Europe and the temperate Far East), it appears highly possible that the species has a wide transpalaearctic distribution.